Design and Implementation of a Web-Based Waste Management Information System to Improve Operational Efficiency at the Environmental Agency of Minahasa Utara Regency - Rolando Ariesky Gans; Juan Mark Jevlands Carlos; Zefanya Mandagi; Ottopianus Mellolo; Sintya Paula Junaedy (International Journal Labs, 2026)
Waste management in Minahasa Utara Regency faces operational challenges including the lack of an integrated digital information system, manual record-keeping processes, and limited real-time monitoring capabilities for waste collection activities. This study presents the design and implementation of a web-based waste management information system for the Environmental Agency (Dinas Lingkungan Hidup) of Minahasa Utara Regency. The system was developed using the PHP Laravel framework with a MySQL relational database and deployed on a local server within the agency's network infrastructure. Key modules implemented include waste collection scheduling, route management, vehicle and personnel tracking, report generation, and a public-facing waste complaint submission portal. The system was evaluated through functional testing using the black-box method and usability testing using the System Usability Scale (SUS) questionnaire administered to 15 agency staff members. Functional testing results show a 100% pass rate across all 42 test cases. The SUS score of 81.3 out of 100 places the system in the